Prevention of aerosol isolation of nontuberculous mycobacterium from the patient's bathroom. Issue 3 (3rd July 2018) - Morimoto, Kozo; Aono, Akio; Murase, Yoshiro; Sekizuka, Tsuyoshi; Kurashima, Atsuyuki; Takaki, Akiko; Sasaki, Yuka; Igarashi, Yuriko; Chikamatsu, Kinuyo; Goto, Hajime; Yamada, Hiroyuki; Kuroda, Makoto; et al.
Recent clinical studies have revealed that reappearance of the same nontuberculous mycobacterium (NTM) infection is common after successful standard treatment [1, 2]. Using pulsed-field gel electrophoresis analysis, Wallace et al . [1] found that ∼75% of Mycobacterium avium - intracellulare complex (MAC) isolates identified after successful treatment are the result of reinfection. According to a recent study conducted by Koh et al . [2] using repetitive sequence-based PCR analysis, all re-identified M.   abscessus subsp. abscessus isolates had a unique genotype. Therefore, patients with NTM are exposed to large amounts of microbes in their daily lives, particularly in cases of reinfection. Reinfection of nontuberculous mycobacterium pulmonary disease may be caused by identical and not different genotypes http://ow.ly/62cH30krdpa